Peran Strategi Metakognitif dengan Bantuan Metode PQ4R pada Prestasi Akademik Mahasiswa PIAUD Di Institut Agama Islam Sunan Giri Bojonegoro - Eshthih Fithriyana (Al Ulya: Jurnal Pendidikan Islam, 2018)
This study is a study study that analyzes the role of metacognitive strategies with the help of the PQ4R method on academic achievement of PIAUD students at the Sunan Giri Bojonegoro Institute of Islamic Religion. Students in this case are students who follow the learning process in higher education who are required to equip themselves with standardized competencies created with academic achievement, as a provision to take positions and support in an increasingly competitive world of work. Based on the results of data analysis of interviews, observations and questionnaires showed that the use of metacognitive strategies with the help of the PQ4R method had a significant role in student academic achievement in cognitive courses.